從PISA與TIMSS國際學測檢視 課程改革與評量機制From PISA and TIMSS to Curriculum Reform and Assessment Reconstruction - 戴維揚Wei-Yang Dai (Higher Education Foundation, 2005)
依「成敗究因」理論，成功者選擇進步的改革策略，失敗者尋找掩飾的藉口。OECD每年研擬國際標準與策略，因應瞬息萬變的挑戰與轉換。PISA國際學測評量結果公布以後，芬蘭、英、美、德、澳等國都經深入廣泛嚴肅地研究檢討，並制定、實施課程改革方案及重新調整評量機制。另就IEA 2003年TIMSS學測成績公布：新加坡取代臺灣，榮獲四冠王，成績最亮麗，全球皆矚目，值得深思、檢討。 教育改革成功要訣，首先要求教師專業成長，教師以身作則，重新啟動良好閱讀習慣，才能帶動學生、學校、家庭親子共讀，建構一個書香社會。芬蘭由於全民享受閱讀、紮實學習，因此2000年PISA三科學測皆排前四名，2003年的PISA四項評量成績皆升為前三名，其中「閱讀」與「科學」皆獲第一，成為全球最優秀的教育改革楷模。德國學測成績並不理想，「知恥近乎勇」，全國總動員，嚴管勤教，果然PISA及TIMSS成績都大幅度提升。美國教改也全面提升TIMSS的成績。相對地，日本、臺灣國際評量名次雖然曾經名列第一，然而近年都連續全面下滑。香港各界知所驚惕，引以為鑑，於2003年公布提升法案，期盼往後成績依然亮麗。臺灣將於2006年首次參與PISA全面評量，並於2006年首次參與IEA的PIRLS國際閱讀素養評比，以及2007年第三次參加TIMSS的評量。本文論述上述8國（地區）一些教改成功的模式，供教育改革與評量機制的方家參考。In this age of standards and assessments, a curriculum designed for primary and secondary schools is the most significant foundation for educational reform. We should start to strengthen strategies and guidances to align standards, curricula, and assessments. OECD issues yearly educational indicators, benchmarks and standards for policy planning and also indicates some major final outcomes in the PISA. Each country or even county goes through some major dramatic educational changes and challenges along with striking social, political and economic developments. Curriculum innovation has resulted in the redesign and reconstruction of new assessment systems and structures. This paper examines eight countries' (areas) curriculum reforms. Their outcomes are documented and compared with those of the PISA and TIMSS regarding various cultural educational policies and planning.